2014
DOI: 10.1002/fld.3893
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution p‐adaptive DG simulations of flows with moving shocks

Abstract: SUMMARYHigh‐order accurate DG discretization is employed for Reynolds‐averaged Navier–Stokes equations modeling of complex shock‐dominated, unsteady flow generated by gas issuing from a shock tube nozzle. The DG finite element discretization framework is used for both the flow field and turbulence transport. Turbulent flow in the near wall regions and the flow field is modeled by the Spalart–Allmaras one‐equation model. The effect of rotation on turbulence modeling for shock‐dominated supersonic flows is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Demonstration is performed first for one-and two-dimensional test problems with exact solutions these cases were computed with threedimensional meshes. For certain cases, the benefits that could be obtained from using p-type refinement 43 to better resolve complex flow structures are demonstrated. Furthermore, adaptive mesh refinement could be employed to achieve crisper resolution of moving discontinuities.…”
Section: Numerical Examplesmentioning
confidence: 98%
“…Demonstration is performed first for one-and two-dimensional test problems with exact solutions these cases were computed with threedimensional meshes. For certain cases, the benefits that could be obtained from using p-type refinement 43 to better resolve complex flow structures are demonstrated. Furthermore, adaptive mesh refinement could be employed to achieve crisper resolution of moving discontinuities.…”
Section: Numerical Examplesmentioning
confidence: 98%
“…Implementation of p‐refinement is performed in a parallel environment, and it is straightforward with the hierarchical Legendre polynomial bases; it is however more complicated for divergence‐free vector bases. Application of both h‐ and p‐adaptivity for the DG method requires information exchange only at the element faces and has been validated and demonstrated that it is conservative and for problems with smooth solutions converges to the design order of accuracy of the scheme . Numerical solutions with p‐adaptivity were also obtained for flows including discontinuities .…”
Section: P‐adaptivitymentioning
confidence: 99%
“…Application of both h-and p-adaptivity for the DG method requires information exchange only at the element faces and has been validated and demonstrated that it is conservative and for problems with smooth solutions converges to the design order of accuracy of the scheme. 52,53 Numerical solutions with p-adaptivity were also obtained for flows including discontinuities. 54 For large scale three-dimensional simulations, it is important to ensure that the parallel efficiency is high during the entire course of the computation.…”
Section: P-adaptivitymentioning
confidence: 99%
“…In compressible, dispersed, multiphase flows we observe the interaction of the macroscopic flow in the following ways: i) with refined structures due to compressibility (e.g. shock and acoustic waves [5,6], thermal effects and chemical reaction regions [7], [8], [9]), ii) with vortical structures [10], and iii) with dispersed micro-scale droplets and particles [11], moving walls and detailed solid structures [12] or solidification interfaces [13].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, this can be achieved by increasing the number of basis functions used for the discretisation of the field variables, resulting in an increase of the degrees of freedom within the element and the order of accuracy of the discretisation (i.e. p-type refinement) [15,16]. Secondly, this can be achieved by local increase of mesh resolution (i.e.…”
Section: Introductionmentioning
confidence: 99%